2001
DOI: 10.1128/mcb.21.13.4197-4207.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intrasteric Inhibition of ATP Binding Is Not Required To Prevent Unregulated Autophosphorylation or Signaling by the Insulin Receptor

Abstract: Receptor tyrosine kinases may use intrasteric inhibition to suppress autophosphorylation prior to growth factor stimulation. To test this hypothesis we made an Asp1161Ala mutant in the activation loop that relieved intrasteric inhibition of the unphosphorylated insulin receptor (IR) and its recombinant cytoplasmic kinase domain (IRKD) without affecting the activated state. Solution studies with the unphosphorylated mutant IRKD demonstrated conformational changes and greater catalytic efficiency from a 10-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…As a typical example, the active and inactive conformation of INSR are mainly due to the orientations of the activation loop, which blocks substrate access to the catalytic cleft in the basal/inactive state while swings away from the orientation of the inactive conformation to form a platform for substrate binding 56 . As demonstrated by previous studies 23 and confirmed in the present study (Fig. 5c), this conformational change could be readily detected by limited trypsin digestion: the activation loop of INSR is susceptible for trypsin cleavage upon activation through ligand and ATP binding but only very weakly in its basal state.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a typical example, the active and inactive conformation of INSR are mainly due to the orientations of the activation loop, which blocks substrate access to the catalytic cleft in the basal/inactive state while swings away from the orientation of the inactive conformation to form a platform for substrate binding 56 . As demonstrated by previous studies 23 and confirmed in the present study (Fig. 5c), this conformational change could be readily detected by limited trypsin digestion: the activation loop of INSR is susceptible for trypsin cleavage upon activation through ligand and ATP binding but only very weakly in its basal state.…”
Section: Discussionsupporting
confidence: 90%
“…5c, INSR was inaccessible to trypsin cleavage in the presence of insulin and ADP. However, the presence of insulin and AMP-PNP enabled the transition of INSR from inactive to active form, which was reported to be liable for trypsin digestion 23,24 and confirmed in the present study. We further demonstrated that the presence of ConA inhibited this conformational activation.
Fig.
…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…A D1161A mutation has been reported, showing that loss of three interactions (1, 2, and 3, Fig. 1) produced an unphosphorylated kinase with increased catalytic efficiency (13,14). The structure of this mutant IRKD displayed a "gate-open" conformation in which the ATP binding site was freed and pseudosubstrate binding of the A-loop was not observed; most residues in the A-loop were disordered.…”
mentioning
confidence: 86%
“…Similarly, alanine substitution of Asp1149 (D1149A), which plays a critical role in blocking substrate access to the active site of IR kinase, increases catalytic efficiency (~10-fold) even more strongly than Y972A. However, in contrast to catalytic efficiency, D1149A has a modest effect (~3-fold) on basal phosphorylation of IR relative to Y972A 22,23 . The difference between the two mutations in basal phosphorylation of the receptor and catalytic efficiency suggests that Tyr972 also plays an important role in conformational rearrangement of β-subunits, allowing trans-autophosphorylation of the receptor.…”
Section: The Juxtamembrane Domain Plays a Key Role In The Restrictionmentioning
confidence: 99%